Mammalian SWI/SNF chromatin remodeler is essential for reductional meiosis in males - Menon, Debashish U.; Magnuson, Terry (bioRxiv, 2020)
BRG1, a catalytic subunit of the mammalian SWI/SNF nucleosome remodeler is essential for male meiosis1. In addition to BRG1, multiple subunits (~10-14) some of which are mutually exclusive, constitute biochemically distinct SWI/SNF subcomplexes, whose functions in gametogenesis remain unknown. Here, we identify a role for the PBAF (Polybromo - Brg1 Associated Factor) complex in the regulation of meiotic cell division. The germ cell-specific depletion of PBAF specific subunit, ARID2 resulted in a metaphase-I arrest. Arid2cKO metaphase-I spermatocytes displayed defects in chromosome organization and spindle assembly. Additionally, mutant centromeres were devoid of Polo-like kinase1 (PLK1), a known regulator of the spindle assembly checkpoint (SAC)2. The loss of PLK1 coincided with an abnormal chromosome-wide expansion of centromeric chromatin modifications such as Histone H3 threonine3 phosphorylation (H3T3P) and Histone H2A threonine120 phosphorylation (H2AT120P) that are critical for chromosome segregation3,4. Consistent with the known role of these histone modifications in chromosome passenger complex (CPC) recruitment, Arid2cKO metaphase-I chromosomes display defects in CPC association. We propose that ARID2 facilitates metaphase-I exit by regulating spindle assembly and centromeric chromatin.